Batata-doce irrigada para a produção de etanol - Nogueira, Cicero Urbanetto (2017)
Sweet potato is an amylaceous root of high potential for use in the production of bioethanol. However, its productivity is intrinsically linked to the environmental and management factors, in which the availability of water in the growing periods and the harvesting period, which were the object of the present study, stand out. Two production trials (2013-2014 and 2014-2015) were installed in the experimental area of the Polytechnic College of the Federal University of Santa Maria-RS, with the variety BRS Cuia (RNC 27.315). The experimental design was a randomized complete block design, with four replications, in a factorial scheme, where the factors were the irrigation slides and the harvesting times. The treatments consisted in the application of 25%, 50%, 75% and 100% of crop evapotranspiration (ETc) irrigation slides and the control treatment (without irrigation). Harvest times were: 90, 120, 150, 180 and 210 days after planting. The experimental unit was formed by 4 m wide and 5 m long (20 m2), total area of 400 m2, without the border plants and the spacing between the lines was one meter with distance between plants within each row of 0.40 m. Irrigation management was based on crop evapotranspiration, according to the methodology proposed by FAO. The irrigation system used was located drip between spacing each emitter and 0.2 m flow of 0.8 L h-1, and the frequency of irrigation was every seven days. It was carried out chemical analysis and physical soil. The monitoring of soil moisture was the time domain reflectometry (TDR). The following parameters were evaluated: the yield; the length; the diameter; root classification; the levels of starch, protein and amylose; and laboratory-scale ethanol production on pilot scale and on a pilot scale conventional process. The sweet potato crop was influenced by the different irrigation slides applied and the harvest times, with increase in starch content and decrease in yield. The best harvest season was 120 to 150 days after planting. Under the conditions of this study the sweet potato crop did not require irrigation. The maximum yield of ethanol obtained on a pilot scale was 195 kg t-1 of solids, 125 g L-1 of sweet potato flour, 4% by weight of enzymes and 36°C, with this yield it was possible to produce 2,654 kg of ethanol per hectare. Due to the rusticity of the crop, management cost, short cycle and starch production, sweet potato proved to be an excellent raw material for the production of ethanol by simultaneous saccharification and fermentation, being an alternative for the energy matrix diversification.